Shallow Calcium Carbonate Cycling in the North Pacific Ocean. Issue 5 (17th May 2022) - Subhas, Adam V.; Dong, Sijia; Naviaux, John D.; Rollins, Nick E.; Ziveri, Patrizia; Gray, William; Rae, James W. B.; Liu, Xuewu; Byrne, Robert H.; Chen, Sang; Moore, Christopher; Martell‐Bonet, Loraine; et al.
Abstract: The cycling of biologically produced calcium carbonate (CaCO3 ) in the ocean is a fundamental component of the global carbon cycle. Here, we present experimental determinations of in situ coccolith and foraminiferal calcite dissolution rates. We combine these rates with solid phase fluxes, dissolved tracers, and historical data to constrain the alkalinity cycle in the shallow North Pacific Ocean. The in situ dissolution rates of coccolithophores demonstrate a nonlinear dependence on saturation state. Dissolution rates of all three major calcifying groups (coccoliths, foraminifera, and aragonitic pteropods) are too slow to explain the patterns of both CaCO3 sinking flux and alkalinity regeneration in the North Pacific. Using a combination of dissolved and solid‐phase tracers, we document a significant dissolution signal in seawater supersaturated for calcite. Driving CaCO3 dissolution with a combination of ambient saturation state and oxygen consumption simultaneously explains solid‐phase CaCO3 flux profiles and patterns of alkalinity regeneration across the entire N. Pacific basin. We do not need to invoke the presence of carbonate phases with higher solubilities. Instead, biomineralization and metabolic processes intimately associate the acid (CO2 ) and the base (CaCO3 ) in the same particles, driving the coupled shallow remineralization of organic carbon and CaCO3 . The linkage of these processes likely occurs through a combination of dissolution due to zooplankton grazing and microbial aerobic respiration within degrading particle aggregates. The coupling of these cycles acts as a major filter on the export of both organic and inorganic carbon to the deep ocean. Plain Language Summary: The marine carbon cycle is made of organic carbon and calcium carbonate (CaCO3 ) components. While the organic carbon cycle has received much attention, the CaCO3 cycle is relatively understudied. Through a dedicated research expedition to the North Pacific Ocean, we demonstrate here a coupling of these two cycles, stemming from the fact that all organisms that produce CaCO3 also produce intimately associated organic carbon. We suggest that the mechanisms responsible for the formation and sinking of organic carbon particles in the ocean are likely as important for CaCO3 export, and that the respiration of organic carbon is responsible for the dissolution of a substantial portion of CaCO3 in the upper ocean. Key Points: High resolution carbonate chemistry, δ 13 C‐DIC, and particle flux measurements in the NE Pacific sheds light on the upper ocean calcium carbonate and alkalinity cycles Based on this sampling campaign, there is evidence for substantial CaCO3 dissolution in the mesopelagic zone above the saturation horizon Dissolution experiments, observations, and modeling suggest that shallow CaCO3 dissolution is coupled to the consumption of organic carbon, through a combination of zooplankton grazing and oxic respiration within particle microenvironments